Faktor-FaktorYang Mempegaruhi KinerjaI Pengerajin Tenun Di Desa Sukarara - Afrian Catur Pramudya; Endang Kartini; Elvina Setiawati (Akuntabel: Jurnal Ilmiah Akuntansi, 2025)
This research aims to find out about the factors that influence performance. This research variable consists of 3 (three) independent variables, namely education level (X1), training (X2), business age (X3) and 1 (one) dependent variable, namely performance. The population of this research is weaving craftsmen in Sukarara Village. The sampling used in this research was simple random sampling. The sample used was 95 respondents. This research uses associative quantitative methods and collects primary data using questionnaire techniques which are measured using a Likert scale. The analysis technique used is multiple linear analysis with IBM SPSS (Statistical Package for Social Science) version 25 software. The results of this research show that the level of education has a positive effect on performance, while training and business age have no effect on performance.